Agronomic Performance and Genotype × Environment Interaction of Herbicide‐Resistant Maize Varieties in Eastern Africa. Issue 2 (1st March 2015) - Makumbi, Dan; Diallo, Alpha; Kanampiu, Fred; Mugo, Stephen; Karaya, Haron
ABSTRACT: Striga hermonthica (Del.) Benth. and Striga asiatica (L.) Kuntze severely affect maize ( Zea mays L.) production in sub‐Saharan Africa. A single Striga plant produces a large number of seeds that form a bank of viable but dormant seed in the soil until they get a chemical signal from suitable maize host roots. Imidazolinone‐resistant (IR) open‐pollinated maize varieties (OPVs) developed for Striga control were tested in diverse environments in four countries of eastern Africa in 2004. The objective of the study was to assess the agronomic performance of IR maize and genotype × environment interactions (GE) for grain yield (GY) and the number of emerged Striga plants across 17 environments under Striga ‐infested and Striga ‐free conditions. In the combined analysis of variance across Striga ‐infested and Striga ‐free locations, mean squares for genotypes and GE were significant for most measured traits. The best IR maize variety (STR‐VE‐216) outyielded the Striga ‐tolerant and commercial genotypes by 113 and 89%, respectively, under Striga ‐infested conditions. IR OPVs supported significantly fewer emerged Striga plants relative to the check varieties. Under Striga ‐free conditions, IR OPVs showed GY advantage over commercial varieties. Under Striga ‐infested conditions genotypic variance ( σ G 2 ) was larger than genotype × location variance ( σ G × L 2 ) for GY and number of emerged Striga plants at 12 wk after planting. The genetic correlations among locations under Striga ‐infested conditions were high (0.990), suggesting little GE between most environments used. Cluster analysis of genotypes under Striga ‐infested locations revealed two major groups that separated the IR OPVs from the check varieties. The outstanding performance of selected IR OPVs indicates that their use for Striga control would reduce the Striga seed bank while benefiting farmers with high GY.